The Role of Blended Learning Models in Mathematics Learning during the COVID-19 Pandemic - Kartika Amelia Cahyanti; Yayu Nurhayati Rahayu; Dedi Mulyadi (Gunung Djati Conference Series, 2022)
The purpose of this study was to determine the process and strategy for implementing the blended learning model in mathematics learning during the COVID-19 pandemic. In this study, the method used is SLR (systematic literature review). Researchers use journals that are relevant to the research conducted to obtain information related to research. The results showed that the blended learning model had a very large impact on mathematics learning during the COVID-19 pandemic because there were changes in the mathematics learning process in terms of understanding the material, solving mathematics learning problems and student evaluation results when compared to other learning methods. The pattern of the blended learning model is applied attractively and very effectively, the learning pattern is carried out face-to-face and online. This can make students motivated by the blended learning model where the learning process has a more flexible time because it can be carried out anytime and anywhere